Time Delay and Cost Overrun in Qatari Public Construction Projects. (2016) - Senouci, Ahmed; Ismail, Alaa; Eldin, Neil
Abstract: This paper investigated cost overruns and delays in Qatari public construction projects. An extensive review of regional and international publications was conducted to get a better understanding of the problem and the various methodologies that were used to analyze it. The data that was collected from Qatar public work authority ASHGHAL included 122 public road, building, and drainage projects. ANOVA method was used for data analysis and inference. A regression analysis was also conducted to establish the relationships between project contract prices and cost overruns and to develop prediction models for estimating cost overruns. Two linear regression models were developed for predicting cost overruns for building and drainage public projects, respectively. Cost overruns for building projects increased with contract prices. On the other hand, cost overruns for drainage projects decreased with increasing contract prices. A significant effort was spent in collecting data on cost overruns and delays in public construction projects. However, data confidentiality did allow the collection of enough data to ensure the robustness of the developed regression prediction models.